Optimal adjustment of control parameters in short‐term operational planning of power systems based on cost‐effective security solutions - Sina Hashemi; Hamid Lesani; Mohammad Reza Aghamohammadi (IET Generation, Transmission & Distribution, 2023)
Abstract Interference amongst stability phenomena has been raising concerns due to the potential maladjustment of control parameters in large‐scale and interconnected power systems. In consequence of such interference, power system security is threatened. In order to preclude any inconsistency and ensure maximum security, a comprehensive study needs to be carried out in short‐term operational planning concentrating on the determination of an economic operating point with enhanced static and dynamic security. In this paper, an integrated approach with incorporation of voltage and rotor‐angle stabilities into the optimal operation of power system is proposed. This study is based on a many‐objective optimisation problem providing a cost‐effective security solution prior to real‐time operation whereby the operating point of power system is maximally secure and economic. The output of the proposed approach is a vector of adaptively adjusted control parameters consisting of terminal voltage and active power of generating units, reactive power of SVCs, and tap position of transformers. In addition, active power production and reactive power opportunity costs, static, and dynamic security criteria constitute the vector of objective functions with eight elements. The performance of the approach is assessed in several scenarios including various load patterns and different power limits of generators.